Communicative Competence in the Structure of "Soft Skills" as Part of the University Students Professional Training - E.N. Vasilyeva; A.V. Scherbakov; M.F. Kuragina (Психолого-педагогические исследования)
Modern society transformation stimulates the search for new self-fulfillment conditions of a professional’s personality. Soft skills, acquired through targeted professional training, are one of the determinants of professional activity growth. Based on the analysis of domestic and foreign literature, in accordance with the Russian Managers Association terminology, the article lists specific communicative competencies of a "successful" manager. As a hypothesis of the study, an assumption was made about the presence of a predominantly low development level of communicative competencies that are included in the structure of students’ professionally significant "soft skills". The study (N=184) involved students aged 18–19 (M=18,28; SD=0,45), including 110 female and 74 male students of the 1st year bachelor Management program from Nizhny Novgorod universities. The following methods were used: the “Level of subjective control” by E.F. Bazhin, E.A. Golynkin, L.M. Etkind; "Emotional intelligence test" by D.V. Lucin; "Сommunicative social competence diagnosis" by N.P. Fetiskin, V.V. Kozlov, G.M. Manuilov. The diagnostic results showed the predominant presence of medium and high development levels of communicative competencies, related to communicative social competence, emotional intelligence and subjective control of future managers. The presence of a medium and high levels of the studied communicative competencies development allows using them as a basis for the successful “soft skills” development of a management specialist.